Achievement Goal and Homework Behavior: Mediator Effects of Achievement Emotion (Jurnal Bimbingan Konseling, 2019)
This study examinedthe effect of achievement goal on homework behavior and achievementemotionas a mediator for high school students in Sukoharjo Regency. Four hundred twenty-fourhigh school students in Sukoharjo Regency by cluster purposive sampling were usedin the study. Mediation analysis was applied to test the effects of achievement emotionmediation on the achievement goal of homework behavior. The results of structural equation modeling show the effects of emotional mediation of pleasure in connecting with concentration and effort. Furthermore, the task approach, task avoidance, and other avoidances directly affect enjoyment; the task approach and other avoidances affect anxiety; the task approach, task avoidance, and enjoymentare influencing business and concentration. The theoretical and practical implications of these findings are discussedin the article.